Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1542/peds.2013-3833
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Guideline to Improve Management of Syncope in the Emergency Department

Abstract: BACKGROUND AND OBJECTIVES: Thirty-five percent of children experience syncope at least once. Although the etiology of pediatric syncope is usually benign, many children undergo low-yield diagnostic testing. We conducted a quality improvement intervention to reduce the rates of low-yield diagnostic testing for children presenting to an emergency department (ED) with syncope or presyncope.METHODS: Children 8 to 22 years old presenting to a tertiary care pediatric ED with syncope or presyncope were included. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 32 publications
1
32
0
3
Order By: Relevance
“…We showed, using time series methodology, a decrease in resource utilisation (radiographs, viral testing and β-agonist therapy) for patients with bronchiolitis without a change in outcomes 29. In addition, we were able to decrease resource utilisation (blood testing and intravenous fluid) and increase rates of pregnancy testing in pubertal girls and ECG testing for patients with syncope 30. In a third publication demonstrating the effectiveness of the programme, we were able to decrease rates of brain imaging for patients with minor head injury, and at a rate faster than that of the national decline 31.…”
Section: Resultsmentioning
confidence: 77%
“…We showed, using time series methodology, a decrease in resource utilisation (radiographs, viral testing and β-agonist therapy) for patients with bronchiolitis without a change in outcomes 29. In addition, we were able to decrease resource utilisation (blood testing and intravenous fluid) and increase rates of pregnancy testing in pubertal girls and ECG testing for patients with syncope 30. In a third publication demonstrating the effectiveness of the programme, we were able to decrease rates of brain imaging for patients with minor head injury, and at a rate faster than that of the national decline 31.…”
Section: Resultsmentioning
confidence: 77%
“…In the first example,61 the improvement team was unable to contact 56 patients for phone or email follow-up (ie, why the data are missing). To account for this missing data, the team performed serial reviews of medical records.…”
Section: Resultsmentioning
confidence: 99%
“…Results of our study demonstrated a measurable short-term improvement in learners' performance similar to those of Guse et al, who showed improved use of diagnostic testing after a quality improvement intervention in syncopal patients. 12 In our project, the key components to achieve competence included interactive session with content expert, peer -peer discussions, and feedback from SPs.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%